Effects of lipid sources, lysophospholipids and organic acids in maize-based broiler diets on nutrient balance, liver concentration of fat-soluble vitamins, jejunal microbiota and performance - Polycarpo, G. V.; Burbarelli, M. F.C.; CarÃo, A. C.P.; Merseguel, C. E.B.; Dadalt, J. C.; Maganha, S. R.L.; Sousa, R. L.M.; Cruz-Polycarpo, V. C. [UNESP]; Albuquerque, R. (Taylor & Francis, 2016)
Three experiments with a 2 × 2 × 2 factorial arrangement were conducted to evaluate maize-based diets for broilers containing different lipid sources [soybean oil (S) or beef tallow (T)] supplemented with or without lysophospholipids and organic acids on nutrient balance (Experiment I, evaluation period of 10–14 d), on liver concentration of fat-soluble vitamins, on jejunal microbiota (Experiment II, sampling at d 14) and on performance (Experiment III, accumulated periods of 1–14, 1–21 and 1–42 d). A total of 1344 male chicks were used. In each experiment, the birds were allotted in a completely randomised design with 8 replications. The lysophospholipids were mainly composed of lysolecithins and the organic acids blend was constituted by lactic (40%), acetic (7%) and butyric acids (1%). An interaction between lipid sources and lysophospholipids was observed on faecal apparent digestibility of lipid (ADL), which improved with lysophospholipids addition in T diets. Broilers fed on S had higher ADL and faecal apparent digestibility of nitrogen-corrected gross energy (ADGEN). It was not possible to demonstrate a significant treatment effect on the liver concentration of vitamins A and E, even with the differences in fatty acid profile between S and T. Enterobacteria values were below the detection threshold. Lysophospholipid supplementation reduced gram-positive cocci in T-fed birds. S diets promoted lower total anaerobe counts compared with T diets, independent of additives. S diets increased BW gain and feed:gain ratio in all evaluation periods. Lysophospholipids and organic acids improved feed:gain ratio at 1–21 d in T diets. Furthermore, main effects were observed for lysophospholipids and organic acids at 1–42 d, which increased BW gain and improved feed:gain ratio, respectively. No positive interactions between additives were found.